Dīwān-i Fānī : Mawsūm bih Ganj Allāh - Khūʾī, Mīrzā Muḥammad Ḥasan Zunūzī, (Miras Maktoob, ISBN: 9789004365452., 2019)
Born in Khūy (Azerbaidjan), Mīrzā Muḥammad Ḥasan Zunūzī Khūʾī (1172-1225/1758-1810) was a traditional Islamic scholar and man of letters who signed his poems as 'Fānī'. He received his basic education in Zunūz, Tabriz and Khūy, leaving for the holy cites of the Shīʿa in Iraq at the age of 23. There he attended the classes of, among others, Āqā Muḥammad Bāqir Bihbihānī (d. 1205/1790) and Mīrzā Muḥammad Mahdī Shahristānī (d. 1215-16/1800-01). He then returned to Khūy where he spent the rest of his life, save for a two-year 'sabbatical' in Mashhad. In Khūy Fānī was a protégé of the local ruler, Aḥmad Khān Dunbul (d. 1200/1785) and his son Ḥusayn Qulīkhān Dunbul (d. 1213/1799). He is the author of a number of works, among them the encyclopaedic Baḥr al-ʿulūm (Persian) and the spiritual Wasīlat al-najāh (Persian). The Persian poems published here are mostly mystical in tone, often inserting terms or concepts taken from astronomy.